Administrative Responsibility - Kovalenko, Larisa (Problems of legality, 2026)
The relevance of the study is due to the dynamic changes in social relations, the reform of public administration and the need to integrate European standards of the rule of law into the administrative tort legislation of Ukraine. The purpose of the article is a comprehensive theoretical study of the institute of administrative responsibility as a specific type of legal responsibility that combines substantive and procedural elements. The work uses dogmatic, historical, comparative-legal and systemic methods of analysis of regulatory acts, scientific literature and judicial practice. As a result, the essence of administrative responsibility, its key functions (punitive, preventive, educational and restorative), and its public-legal nature, which is implemented through state coercion measures by authorized bodies, are revealed. The administrative offense as the main basis for liability, its features (illegality, guilt, social harm) and elements of composition (object, objective side, subject, subjective side) are analyzed in detail. Current problems of regulatory framework are identified: the conceptual obsolescence of the main codified act of 1984, fragmentation of regulation, duplication of norms in special laws and insufficient compliance of procedures for bringing to liability with the standards of the right to a fair trial. The prospects for improvement through the adoption of a new code on administrative misdemeanors, unification of norms, differentiation of penalties, introduction of alternative sanctions and strengthening of procedural guarantees of individual rights are substantiated, which will increase the efficiency of public administration and the level of citizens’ trust in the state. Prospects for further research are related to assessing the practical effectiveness of the new model of administrative responsibility after its implementation.